Tropical Skin Infections Among Israeli Travelers - Solomon, Michal (The American Society of Tropical Medicine and Hygiene, 2011)
Infectious skin disorders are common dermatologic illnesses in travelers. Knowledge of post-travel–related infectious skin disorders will allow for effective pre- and post-travel counseling. All cases of returning travelers seen in our center seeking care for infectious skin diseases were included in this study. For a comparison, data on returned travelers with non-infectious skin diseases and healthy travelers who had pre-travel consultations in our institution were also analyzed. Altogether, skin-related diagnosis was reported in 540 ill travelers, and among them, 286 (53%) had infectious skin diseases. Tropical skin infection was diagnosed in 64% of the infectious cases. Travelers returning from Latin America were significantly more ill with tropical skin infections than those traveling to Asia and Africa, The most common diagnoses were cutaneous leishmaniasis, myiasis, and cutaneous larva migrans. In conclusion, tropical skin infections are common among Israeli travelers, especially among those who visited Latin America.